Determinants of Entrepreneurial Attitudes and Intentions Among High School Students in Iligan City - F. RESURRECCION, PAMELA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Entrepreneurship has been considered by a lot of developing and underdeveloped countries as one possible solution to address poverty issues. Many governments have not been remiss in initiating programs and campaigns to promote entrepreneurial activities, especially among the young to encourage them to be active contributors to the thrust of poverty alleviation. Despite these efforts, mindsets of students still appear to be focused on corporate employment. This study inquires into possible factors influencing entrepreneurial attitudes and ultimately their intention to pursue an entrepreneurial career. By using correlation statistics, it was found that a mother’s occupations; a father’s highest level of education; curriculum; how important determination, persistence, interest, and energy were to respondents; self-ratings on intelligence and honesty; how strongly respondents agreed that starting a business would mean they could work the hours they wanted and have the control that came from being one’s own boss; and how strongly they agreed that a business degree was necessary to start a business all have positive relationships with the students intention to pursue entrepreneurial endeavors. It was further found that students generally have a favorable attitude towards entrepreneurs and entrepreneurship